Throughput quantitative analysis of EDCA 802.11e in different scenarios - Pérez, Santiago Cristóbal (2013)
This document presents a quantitative analysis of the direct and relative throughput of IEEE 802.11e. The global throughput of an 802.11e WLAN is determined by EDCA (Enhanced Distributed Channel Access) parameters, among other aspects, that are usually configured with predetermined and static values. This study carefully evaluates the Quality of Service (QoS) of Wi-Fi with EDCA in several realistic scenarios with noise and a blend of wireless traffic (e.g., voice, video, and best effort, with Pareto distribution). The metrics of the benefits obtained in each case are compared, and the differentiated impact of network dynamics on each case is quantified. The results obtained show that the default settings are not optimal, and that with an appropriate selection, can be achieved improvements of the order of 25 %, according to the type of traffic. In addition, it could be shown the quantitative impact of each parameter EDCA on the overall performance. This study proposes a new experimental scenario based on the relative proportion of traffic present in the network. Stations have been simulated using the Möbius tool, which supports an extension of SPN (Stochastic Petri Networks), known as HSAN (Hierarchical Stochastic Activity Networks).